Acute presentation of autoimmune hepatitis: a multicentre study with detailed histological evaluation in a large cohort of patients. Issue 11 (20th April 2017) - Nguyen Canh, Hiep; Harada, Kenichi; Ouchi, Hirofumi; Sato, Yasunori; Tsuneyama, Koichi; Kage, Masayoshi; Nakano, Masayuki; Yoshizawa, Kaname; Takahashi, Atsushi; Abe, Masanori; Kang, Jong-Hon; Koike, Kazuhiko; et al.
Abstract : Aims: Although liver biopsy is crucial to diagnose and guide treatment decisions, a detailed histological analysis of autoimmune hepatitis (AIH) with clinically acute presentations has not yet been performed. This study aimed to characterise the histological features and explore potential histological hallmarks to diagnose the acute presentation of AIH. Methods: We systematically evaluated liver specimens of 87 adult patients with acute presentation of AIH retrospectively enrolled from Japanese multicentre facilities. Each histological feature was predefined by consensus based on the diagnostic criteria. Results: Key findings were that acute presentation of AIH revealed histological features of both acute hepatitis and chronic hepatitis accompanying various degrees of fibrosis. The prominent features were lobular necrosis/inflammation (97.7%), plasma cell infiltration (96.4%), emperipolesis (89.3%), pigmented macrophages (84.5%), cobblestone appearance of hepatocytes (82.6%) and perivenular necroinflammatory activity, including centrilobular necrosis (81.4%). Conclusions: The acute presentation of AIH represents the entire histological spectrum of acute hepatitis and chronic hepatitis with various activity grades and fibrosis stages that clinically correspond to acute-onset AIH and acute exacerbation of classic AIH, respectively. Although there are no pathognomonic features for the pathological diagnosis, the prominent presence of lobular and perivenular necroinflammatory activity, pigmented macrophages and cobblestone appearance of hepatocytes in addition to the classic AIH features, such as plasma cell infiltration and emperipolesis, are useful for the pathological diagnosis of the acute presentation of AIH.